2021
DOI: 10.2355/isijinternational.isijint-2020-492
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residual Stress on Hydrogen Embrittlement of a Stretch-Formed Tempered Martensitic Steel Sheet

Abstract: The effects of residual stress on the hydrogen embrittlement behavior of a tempered martensitic steel sheet with 1-GPa-class tensile strength stretch-formed by a hemisphere punch simulating press-formed automotive structural parts were investigated. Cracking on the stretch-formed specimen induced by potentiostatic hydrogen charging was initiated in the foot of the impression of the specimen and propagated to the radial direction both toward the hillside and the plain. The mixture of quasi cleavage and intergra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…自動車の衝突安全性の向上や車両重量の軽量化による省 エネルギー化を目的として,自動車用鋼板は近年高強度化 されており,引張強度 980 MPa を超える高強度鋼板が実用 化されている。しかし,鉄鋼材料は引張強度が 980 MPa を 超えると水素脆化の発現が問題となる 1,2) 。これまで自動車 用鋼板の水素脆化特性は,通常ひずみ速度引張試験 [3][4][5][6]) や, 低ひずみ速度引張試験 7-9) ,定荷重試験 10,11) などで評価され てきた。しかし,自動車用高強度鋼板の多くは各種部品形 状にプレス成形して使用されるので,プレス成形にともな い残留応力や塑性ひずみが導入される 12) 。さらに,残留応 力勾配や塑性ひずみによって鋼内部での水素拡散は促進ま たは抑制され,その結果水素の局在化が起こる。したがっ て,プレス成形が施された高強度鋼板の水素脆化特性は, 残留応力や塑性ひずみ,水素拡散挙動や局所水素量の影響 を考慮して評価する必要がある。 プレス成形鋼板の水素脆化特性については Toji らが U 曲 げ試験片を用いて,塑性ひずみ,負荷応力と侵入水素量が 水素脆化特性へ与える影響を検討している 13) 。その結果, 負荷応力が高く,塑性ひずみが大きく,侵入水素量が多い 条件で割れが発生すると報告している。また,著者らはこ れまでに,U 曲げ加工 14,15) や張出し加工 12,16) 17) はこれまでに水素マイ クロプリント法 [18][19][20] ,銀デコレーション法 [21][22][23][24][25] ,二次イオ ン質量分析法 [26][27][28][29] や表面電位測定 [30][31][32][33][34] を用いる方法などの いくつかの方法が提案されている。これらの方法は高解像 度で鋼材中の水素分布を得ることができる。中でも表面電 位測定を用いるケルビンプローブフォース顕微鏡は,高い 空間分解能に加えて時間分解能を持つことが報告されてい る [30][31][32][33] 。これらの方法は高空間分解能を生かして主に金属 の微細組織に着目したミクロな水素分布の検出に用いられ ている。一方,サブミリ以上のマクロな水素分布を観察す る方法は,表面電位を用いる走査型ケルビンプローブ 34) や 金属酸化膜 35)…”
Section: 緒言unclassified
“…自動車の衝突安全性の向上や車両重量の軽量化による省 エネルギー化を目的として,自動車用鋼板は近年高強度化 されており,引張強度 980 MPa を超える高強度鋼板が実用 化されている。しかし,鉄鋼材料は引張強度が 980 MPa を 超えると水素脆化の発現が問題となる 1,2) 。これまで自動車 用鋼板の水素脆化特性は,通常ひずみ速度引張試験 [3][4][5][6]) や, 低ひずみ速度引張試験 7-9) ,定荷重試験 10,11) などで評価され てきた。しかし,自動車用高強度鋼板の多くは各種部品形 状にプレス成形して使用されるので,プレス成形にともな い残留応力や塑性ひずみが導入される 12) 。さらに,残留応 力勾配や塑性ひずみによって鋼内部での水素拡散は促進ま たは抑制され,その結果水素の局在化が起こる。したがっ て,プレス成形が施された高強度鋼板の水素脆化特性は, 残留応力や塑性ひずみ,水素拡散挙動や局所水素量の影響 を考慮して評価する必要がある。 プレス成形鋼板の水素脆化特性については Toji らが U 曲 げ試験片を用いて,塑性ひずみ,負荷応力と侵入水素量が 水素脆化特性へ与える影響を検討している 13) 。その結果, 負荷応力が高く,塑性ひずみが大きく,侵入水素量が多い 条件で割れが発生すると報告している。また,著者らはこ れまでに,U 曲げ加工 14,15) や張出し加工 12,16) 17) はこれまでに水素マイ クロプリント法 [18][19][20] ,銀デコレーション法 [21][22][23][24][25] ,二次イオ ン質量分析法 [26][27][28][29] や表面電位測定 [30][31][32][33][34] を用いる方法などの いくつかの方法が提案されている。これらの方法は高解像 度で鋼材中の水素分布を得ることができる。中でも表面電 位測定を用いるケルビンプローブフォース顕微鏡は,高い 空間分解能に加えて時間分解能を持つことが報告されてい る [30][31][32][33] 。これらの方法は高空間分解能を生かして主に金属 の微細組織に着目したミクロな水素分布の検出に用いられ ている。一方,サブミリ以上のマクロな水素分布を観察す る方法は,表面電位を用いる走査型ケルビンプローブ 34) や 金属酸化膜 35)…”
Section: 緒言unclassified
“…Previously, the authors of the present study investigated the effects of residual stress and plastic strain on the hydrogen embrittlement properties of press-formed specimens, such as U-bend specimens 14,15) and stretch-formed specimens. 12,16) The results showed that the location of the maximum circumferential stress of the stretch-formed specimen of a 1000-MPa-class quenched and tempered martensitic steel corresponded to the crack initiation site, indicating that the residual stress primarily affected the hydrogen embrittlement crack initiation. Thermal desorption spectroscopy results of the stretch-formed specimens after hydrogen charging revealed that the diffusible hydrogen 4…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effects of residual stress and plastic strain must be considered when evaluating the hydrogen embrittlement properties of automobile steel components. In this regard, the deep-drawing test [10][11][12][13] , stretchforming test [14][15][16] , and U-bending test [17][18][19][20][21][22][23] coupled with hydrogen charging have been applied as practical evaluation methods.…”
Section: Introductionmentioning
confidence: 99%